Holistic Character Formation through Islamic Religious Education in Elementary Schools: Integrating Faith, Knowledge, Akhlaq, and Action - Julianah, Miss; Elihami, Elihami; Hanafie Das, Supriadi St. Wardah (Mahaguru: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
Character formation is a central mandate of elementary education because educational success involves not only cognitive achievement but also students’ ability to internalize values, build social relationships, and make ethical decisions. This article formulates a holistic character-formation framework through Islamic Religious Education (IRE) that is relevant to elementary schools. An integrative literature review was conducted using 20 verified key sources published between 2017 and 2024, covering Islamic religious education, character education, social-emotional learning, values education, school culture, and teacher modeling. The sources were examined through thematic coding and conceptual synthesis. The review indicates that character formation through IRE is strengthened when four elements—faith, knowledge, moral conduct, and action—are connected through three pedagogical mechanisms: exemplary and caring teacher-student relationships; reflective, active, and contextual learning; and a consistent school culture supported by families and communities. This framework supports the development of integrity, empathy, social responsibility, critical thinking, and moral resilience in digital environments. The study implies that IRE teachers, classroom teachers, and elementary teacher education programs should develop character ecosystems that move beyond value transmission by providing authentic experiences, reflection, habituation, and cross-context collaboration.